2021
DOI: 10.3389/fpsyg.2021.656412
|View full text |Cite
|
Sign up to set email alerts
|

Peer Relationships and College Students’ Cooperative Tendencies: Roles of Interpersonal Trust and Social Value Orientation

Abstract: The current study investigated the relationship between peer relationships and cooperative tendencies in college students, and explored the mediating role of interpersonal trust and the moderating role of social value orientation in that relationship. A questionnaire was distributed to 406 college students, and the results showed that: (1) peer relationships significantly positively predicted cooperative tendencies; (2) interpersonal trust partially mediated the relationship between peer relationships and coop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 50 publications
(45 reference statements)
0
15
0
4
Order By: Relevance
“…Therefore, students with better peer relationships are more likely to have better sleep quality [ 62 ], and thus, a lower risk of depression. Second, medical students are more inclined to share various things happening in their lives with their peers, including when they feel pressure or are confused [ 64 ]. It can be inferred that students with good peer relationships release stress effectively through talking, thus reducing the probability of depression [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, students with better peer relationships are more likely to have better sleep quality [ 62 ], and thus, a lower risk of depression. Second, medical students are more inclined to share various things happening in their lives with their peers, including when they feel pressure or are confused [ 64 ]. It can be inferred that students with good peer relationships release stress effectively through talking, thus reducing the probability of depression [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Assim, as mulheres parecem ter uma melhor qualidade relacional com os pares. Face a este resultado as jovens do sexo feminino recorrerem mais aos pares como fonte de suporte emocional comparativamente com jovens do sexo masculino, estando mais disponíveis para a partilha e a proximidade emocional (Granja & Mota, 2018;Laghi et al, 2016;Raboteg-Saric & Sakic, 2014), e o desenvolvimento de competências interpessoais focalizadas na comunicação e confiança (Wang & Hu, 2021).…”
Section: Discussionunclassified
“…Nesta medida, a perceção de um estilo parental pautado pela exigência e pelo controlo excessivo, onde prevalece a obediência por poder, a restrição de autonomia, a autoridade e uma baixa afetividade, particularmente face à figura paterna sugere que os jovens desenvolvam perceções inseguras sobre a sua imagem e a relação com os demais (Clark et al, 2015). A insegurança nas relações pode conduzir os jovens a uma necessidade apelativa por realce, ou ao invés disso conduzir à inércia e ao conformismo, que se espelha na fuga através dos consumos de álcool (Wang & Hu, 2021). O estilo permissivo (indulgência) por sua vez prediz positivamente a motivação de consumo de álcool por motivo social, realce, coping e conformidade.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A recent line of theoretical and empirical research has shown that a range of factors can influence interpersonal trust such as social class, 7 social identity complexity, 8 peer relationships, 9 and emotion. 10 However, although interpersonal trust is influenced by various correlates, research is yet to explore the relationship between competency and personality traits for interpersonal trust.…”
Section: Introductionmentioning
confidence: 99%